Healthy snacks and their use in reducing anemia in Peruvian school-age children - Zambrano-Cabanilllas, Abel Walter; Paredes-Sabroso, Silvana Andrea; Candela-Díaz, José Eduardo; Gamero-Collado, Betty; Marín-Machuca, Olegario (Edelweiss Applied Science and Technology, 2025)
The objective of this research is to analyze the use of healthy snacks fortified with iron and to evaluate their effectiveness as a strategy to reduce anemia. Anemia is a significant public health issue that affects a large number of children in Peru, particularly those of school age. It is characterized by a deficiency in the production of red blood cells, which can have serious consequences for both physical and cognitive development. The methodology focused on implementing programs for the development of fortified snacks, offering an alternative dietary option for school-age children. These programs applied fundamental concepts of food technology and included training initiatives for caregivers and food producers. The results obtained relate to the iron content (mg/100g), production weight (g), main ingredients, and type of snack. Evidence indicates that anemia among Peruvian children aged 1 to 59 months is primarily due to nutritional deficiencies, particularly protein deficiency, as well as family cultural practices and various demographic, sociocultural, and socioeconomic factors. The study concludes that the program’s results facilitate active participation from parents, despite some differences in engagement levels. Notably, a significant level of participation in the feeding program was observed, demonstrating that parents are genuinely interested in the well-being of their children and are willing to support nutritional interventions.